Fashion Brand Communication: Research on Marketing Strategies and Audience Construction of Fashion Luxury Brands on Weibo Platform - Xiao, ZeXin (Transactions on Social Science, Education and Humanities Research, 2025)
The popularity of social media in China is increasing, and Weibo is one of the most representative platforms due to its large user base. Weibo is one of the important platforms for fashion luxury brands to conduct marketing and promotion in China. This article uses case analysis to explore and analyze the marketing strategies and audience building of fashion luxury brands on Weibo in recent years. It analyzes and discusses their content production, celebrity endorsements or collaborations, interactive marketing strategies, localization strategies, and brand community building. This article finds through case analysis that fashion luxury brands commonly use localized content and build rich brand stories in their marketing strategies on the Weibo platform to stimulate emotional resonance among audiences. Moreover, fashion luxury brands also increase brand exposure and discussion through more diverse interactive methods and find celebrity endorsements, thereby increasing brand content output and user brand awareness. In addition, the high participation and brand identification tendency of Weibo’s audience towards fashion luxury brands on the Weibo platform provides an opportunity for fashion luxury brands to respond to user feedback and complete content co-creation and audience construction in this process. This study helps fashion luxury brands understand their marketing strategies in the Chinese digital media environment and provides theoretical and practical references for the marketing of fashion luxury brands on Chinese social media platforms in the future.